The Correlation Between Students’ Ability of Simple Past Tense and Their Ability in Writing Recount Text by the Eight Grade Students of SMP Negeri 27 Samarinda in 2017/2018 Academic Year - Novia Indri Arumsari; Yuni Utami Asih; Didik Sucahyo (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2018)
The ability to write recount text is one of communicative competences that should be mastered by the eighth grade students of Junior High School. In writing recount text, simple past tense plays as an important role. The simple past tense should be mastered in order to be able to write recount text well. The purpose of this study was to find out the correlation between two variables, simple past tense ability and writing recount text ability, the researcher conducted the correlation research. The population of this study is the eighth grade students of SMP Negeri 27 Samarinda. There are 200 students and 30 students taken as the samples, a random sampling is applied. The researcher used two kinds of tests, simple past tense test and writing recount text test. In simple past tense test, she used objective test in a form of filling the blanks, while in writing test, she asked students to write a recount text based on their unforgettable experience or their special day. Before the instrument was used, she had to try out the simple past tense test. The main purpose was to find out the difficulty index, validity and reliability of the items of simple past tense test. This study reveals that there is significant correlation between students’ ability of simple past tense and their ability in writing recount text by the eight grade students of SMP Negeri 27 Samarinda in 2017/2018 Academic Year. It is proved by the mean score in simple past tense is 45.86 and mean score in writing recount text is 44.93, the qualification both scores are fair. The data statistically calculate using Pearson Product Moment Formula. The obtained rvalue was 0.861 and the critical value for N= 30 was 0.361. It means that the result obtained from the calculation is greater than critical value. Based on the hypothesis testing, it is found that the value of the calculate t is 9.121, while the critical value of t table with 5% significance with df =29 is 2.045. The value t is higher than t table or 9.121>2.045, it means that the alternative hypothesis is accepted, while the null hypothesis is rejected. This fact was based on the result of the test. Most of the students who had good scores in simple past tense test also got good scores in writing recount text ability test. Based on the result of this study, the researcher suggests the students to master the simple past tense if they want to write recount text better